Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Literasi Matematika Aljabar Berdasarkan Langkah Polya - Rayhana, Rayhana; Nur Yuliany; Anggraeni.A, Putri Mahgfira; Nuhdia; Inzani, Rezki Nur; Haeruddin, Muhammad Ikhsan (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Student difficulties in solving mathematical literacy problems significantly affect elementary school students, which is why this research aims to analyze the difficulties faced by fourth-grade students in solving mathematical literacy problems related to algebra and to formulate strategies to address these difficulties based on Polya's Steps. This study uses a qualitative descriptive method with four fourth-grade students from Class IV-A, selected from 21 students at SD Negeri Bontoramba during the second semester of the 2023/2024 academic year, as the research subjects. Data collection techniques include administering tests and conducting interviews. The researcher uses data reduction, data representation, and conclusion-drawing models for data analysis. The study results indicate that students face difficulties in solving mathematical literacy problems related to algebra, especially in understanding the problem, planning, executing the plan, and reviewing the solution according to Polya's Steps. Students often struggle with understanding the problem, creating models, following procedures, and reviewing results. Keywords: Mathematical Literacy, Student Difficulties, Polya's Theory